1990
DOI: 10.1002/1097-0142(19900315)65:6<1391::aid-cncr2820650624>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and therapeutic significance of the flow cytometric nuclear DNA content in non-small cell lung cancer

Abstract: To evaluate prognostic and therapeutic significance, tumor DNA content was determined by flow cytometry in 310 paraffin-embedded tissue samples obtained surgically from 130 patients with non-small cell lung cancer. Ninety-six (76.8%) patients had DNA aneuploid patterns that were statistically higher in adenocarcinoma than in squamous cell carcinoma. A better 5-year survival rate was observed in Group A (DNA diploidy, 69.6%) than in Group B (DNA aneuploidy and DNA peridiploidy, 33.2%; P less than 0.001). The su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(31 citation statements)
references
References 20 publications
2
29
0
Order By: Relevance
“…In particular, the independence of P53 expression and cell proliferation, as observed for other tumour types (Silvestrini et al, 1993;Costa et al, 1995), supports the hypothesis that P53 has other biological functions in addition to cell -cycle regulation. Moreover, except for a relation between cell proliferation and histology, such biological variables were independent of pathological characteristics, in agreement with previous data (Kerr et al, 1983;Alama et al, 1990;Isobe et al, 1990;Miyamoto et al, 1991;Silvestrini et al, 1991;Filderman et al, 1992;Quinlan et al, 1992;M0rkve et al, 1993;Scagliotti et al, 1993;Ebina et al, 1994;Passlick et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In particular, the independence of P53 expression and cell proliferation, as observed for other tumour types (Silvestrini et al, 1993;Costa et al, 1995), supports the hypothesis that P53 has other biological functions in addition to cell -cycle regulation. Moreover, except for a relation between cell proliferation and histology, such biological variables were independent of pathological characteristics, in agreement with previous data (Kerr et al, 1983;Alama et al, 1990;Isobe et al, 1990;Miyamoto et al, 1991;Silvestrini et al, 1991;Filderman et al, 1992;Quinlan et al, 1992;M0rkve et al, 1993;Scagliotti et al, 1993;Ebina et al, 1994;Passlick et al, 1994).…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have attempted to define the prognostic role of DNA ploidy in patients with all NSCLC histologies and at all stages (Volm et al, 1985;Isobe et al, 1990;Miyamoto et al, 1991;Filderman et al, 1992;M0rkve et al, 1993). Most studies have shown a worse prognosis for patients with aneuploid than for those with diploid tumours (Volm et al, 1985;Isobe et al, 1990;Miyamoto et al, 1991;Filderman et al, 1992), but contrasting results are not lacking (Cibas et al, 1989;M0rkve et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 35 studies fulfilled the criteria of selection (Zimmerman et al, 1987;Tirindelli-Danesi et al, 1987;Ten Velde et al, 1988;Volm et al, 1988;Yamaoka et al, 1989;Cibas et al, 1989;Dazzi et al, 1990;Isobe et al, 1990;Sahin et al, 1990;Shiota et al, 1990;Miyamato et al, 1991;Mizumoto et al, 1991;Liewald et al, 1992;Ogawa et al, 1992;Filderman et al, 1992;Morkve et al, 1993;Cheon et al, 1993;Pence et al, 1993;Rice et al, 1993;Ichinose et al, 1993;Lima et al, 1993;Shimizu et al, 1993;Yu et al, 1993;Usuda et al, 1994;Salvati et al, 1994;Tanaka et al, 1995;Pujol et al, 1996;Huang et al, 1996;Nagai et al, 1996;Jeanfaivre et al, 1997;Muguerza et al, 1997;Kolodzeijski et al, 1997;Graziano et al, 1997;Dalquen et al, 1997;Asamura et al, 1999; (Table 1)). Among the 4033 assessable patients, 2626 suffered from NSCLC with aneuploid DNA content (overall frequency of aneuploidy: 0.65; 95% Cl: (0.64-0.67)).…”
Section: Resultsmentioning
confidence: 99%